Advances in Thin Films, Nanostructured Materials, and Coatings Selected Papers from the 2018 International Conference on "Nanomaterials: Applications & Properties" - Pogrebnjak, Alexander D.; Novosad, Valentine; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book highlights the latest advances in chemical and physical methods for thin-film deposition and surface engineering, including ion- and plasma-assisted processes, focusing on explaining the synthesis/processing-structure-properties relationship for a variety of thin-film systems. It covers topics such as advances in thin-film synthesis; new thin-film materials: diamond-like films, granular alloys, high-entropy alloys, oxynitrides, and intermetallic compounds; ultra-hard, wear- and oxidation-resistant and multifunctional coatings; superconducting, magnetic, semiconducting, and dielectric films; electrochemical and electroless depositions; thin-film characterization and instrumentation; and industrial applications.
Thin Film Deposition by Plasma Beam of a Vacuum Arc with Refractory Anodes -- Multilayer Design of CrN/MoN Superhard Protective Coatings and Their Characterisation -- Structure and Properties of Combined Multilayer Coatings Based on Alternative Triple Nitride and Binary Metallic Layers -- DSC Investigations of the Effect of Annealing Temperature on the Phase Transformation Behaviour -- Microstructure and Mechanical Properties of Multilayered αAlN/α-BCN -- Mass Transfer Model of Sputtering from Rod-Like Targets for Synthesis of Multielement Nanocoatings -- Self-Organized Growth by Sputtering and Other PVD Techniques -- On the Possibility of Training Demonstration of the Giant Magnetoresistance Effect in Higher School -- Multifractal analysis of the surfaces of protective (TiAlSiY)N, Me1-xN/CrN and Me1-xN/ZrN coatings.
Keywords: Surfaces (Technology).; Thin films; Microtechnology; Microelectromechanical systems; Surfaces (Physics).; Nanochemistry; Materials -- Analysis; Materials; Surfaces, Interfaces and Thin Film; Microsystems and MEMS; Surface and Interface and Thin Film; Nanochemistry; Characterization and Analytical Technique; Materials Engineering